Delayed onset of right congenital diaphragmatic hernia associated with Group B streptococcal sepsis in a neonate - Lalit Parida (Wolters Kluwer Medknow Publications, 2016)
A full-term male neonate was initially managed for respiratory distress which developed few hours after birth. His initial chest radiograph was normal, and blood culture revealed Group B streptococcal (GBS) sepsis. He subsequently developed progressive right chest opacification that did not improve with medical management. Imaging done few days later revealed right-sided diaphragmatic hernia. The 12-day-old neonate underwent primary repair of the diaphragmatic defect and had an uneventful recovery. This case report intends to highlight this unique association between early onset GBS sepsis and delayed onset of the right congenital diaphragmatic hernia.